2012
DOI: 10.1186/2036-7902-4-15
|View full text |Cite
|
Sign up to set email alerts
|

The sonographic digital portfolio: a longitudinal ultrasound image tracking program

Abstract: BackgroundUltrasonography (US) at the medical student level is developing. As clinical skills and simulation centers expand, US equipment miniaturizes, and more students are exposed to ultrasound; a digital portfolio comprised of US images and videos may be useful in demonstrating experience and possibly competency.MethodsMedical students participated in US curricula consisting of didactics and hands-on training. From 1 July 2006 to 30 June 2008, student images and videos were saved. Total images and videos we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 9 publications
0
17
0
1
Order By: Relevance
“…Online and e-learning technologies [117,118] In a written exam taken prior to a hands-on ultrasound course, Hempel et al [117] report that students who took part in a case-based e-learning course performed better than those who were taught with a classroom-based presentation; Hughes et al [118] described benefits for students in collating a portfolio of ultrasound images as a means of tracking their learning and development.…”
Section: Learning Category-incorporation Of Ultrasound Into Teaching mentioning
confidence: 99%
“…Online and e-learning technologies [117,118] In a written exam taken prior to a hands-on ultrasound course, Hempel et al [117] report that students who took part in a case-based e-learning course performed better than those who were taught with a classroom-based presentation; Hughes et al [118] described benefits for students in collating a portfolio of ultrasound images as a means of tracking their learning and development.…”
Section: Learning Category-incorporation Of Ultrasound Into Teaching mentioning
confidence: 99%
“…Probablemente hay que empezar a plantearse la necesidad de establecer una serie de cambios en los contenidos y objetivos de los planes de estudio en Medicina, así como determinar la forma de educación y evaluación de la ecografía, considerando por ejemplo si sería beneficioso incluir los cortes tomados en los sistemas PACS («Picture Archiving and Communication System») de los hospitales universitarios para facilitar el seguimiento y acceso por parte de profesores y alumnos 21 .…”
Section: Discussionunclassified
“…17 To track image accuracy over time, an ultrasound digital portfolio may be useful to document the student's US longitudinal experience. 24 Most of the respondents provided positive opinions regarding US education, and all of the radiology elective students had used US more frequently after they finished the elective radiology course. This may have an impact on the improvement of patient care.…”
Section: Mean Score Sd Pmentioning
confidence: 97%
“…Some studies used an US simulator as a teaching model. 9,24 Parks et al 9 demonstrated that medical students without previous formal US training achieved a degree of competency in simulated PoCUS after a short training period using a PoCUS simulator. However, an US simulator allows students unrestricted access to practice their US skills.…”
Section: Mean Score Sd Pmentioning
confidence: 99%